The Effect of Diversification Strategy on Performance of Companies Listed In the Nairobi Securities Exchange - Ondari, Emily N.; Awino, Zachary Bolo; Machuki, Vincent N. (Archives of Business Research, 2016)
A fundamental question in corporate strategy is the choice of horizontal scope – the set of industries and market segments in which a firm competes. Governing this choice is a trade-off between the threat of losing focus and the opportunity to grow and exploit synergies. This trade-off raises the question of whether and when diversification is profitable. Diversification has been inconclusively linked to organizational performance and no consensus has yet emerged. The objective of this study was to establish the effect of diversification strategy on performance of companies listed at the Nairobi Securities Exchange in Kenya. A census survey was carried out on all the 59 publicly quoted companies out of which 35 responded indicating a response rate of approximately 60%. The study reveals statistically significant results for the influence of diversification strategy on non-financial measures of organizational performance and statistically not significant results on financial performance. Specifically, diversification relatedness had a statistically significant effect on organizational performance whereas mode of entry into diversification did not have a statistically significant effect. This study has contributed to the general body of knowledge by providing empirical findings for the context of companies listed at the NSE a context which is largely unexplored in literature with regard to diversification strategies. For policy makers, the study implies that diversification is an effective strategy for improving firm performance. The results of this study can be used in policy development in the areas of business growth strategies and priority diversification areas for business firms. Managers can use the findings of this study to identify performance drivers in their respective organizations. More importantly, managers should establish which diversification strategy will lead to a sustainable competitive advantage. One of the main drawbacks of this study was that the financial performance indicators (Earnings per Share and Profit before Tax) yielded statistically not significant results when they were regressed with diversification strategy. The study therefore considered only non-financial measures of firm performance. Secondly, the study employed a cross sectional approach whereas a longitudinal approach would provide for a longer time of study to observe relationships among study variables. Future research studies can use organizational characteristics as moderators to gain further insights into the relationship between diversification strategy and organizational performance.